2013
DOI: 10.1080/17441692.2012.762412
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of vaginal microbicides among female sex workers and their intimate male partners in two Mexico–US border cities: A mixed methods analysis

Abstract: Background Female sex workers (FSWs) may benefit from pre-exposure prophylaxis (PrEP) including microbicides for HIV prevention. Since adherence is a key factor in PrEP efficacy, we explored microbicide acceptability and potential barriers to use within FSWs’ intimate relationships in Tijuana and Ciudad Juárez, Mexico, where HIV prevalence is increasing. Methods FSWs and their verified intimate (non-commercial) male partners completed quantitative and qualitative interviews from 2010–2012. Our complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…The present analysis also demonstrated that condom use did not significantly change over time among these couples in Tijuana; however, there was a trend towards decreasing condom use among couples in Ciudad Juarez that did not reach statistical significance ( p < 0.1). These results are consistent with previous research among FSWs in India and Mexico in which condom use with noncommercial male partners is low, steady over time, and difficult to change through interventions (Ramesh et al, 2010; Ulibarri et al, 2012), suggesting the need for alternative prevention strategies to replace or supplement condom use, including pre-exposure prophylaxis in oral or topical microbicide form combined with enhanced HIV/STI risk communication skills and male involvement in prevention and health promotion efforts (Roberson et al, 2013). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present analysis also demonstrated that condom use did not significantly change over time among these couples in Tijuana; however, there was a trend towards decreasing condom use among couples in Ciudad Juarez that did not reach statistical significance ( p < 0.1). These results are consistent with previous research among FSWs in India and Mexico in which condom use with noncommercial male partners is low, steady over time, and difficult to change through interventions (Ramesh et al, 2010; Ulibarri et al, 2012), suggesting the need for alternative prevention strategies to replace or supplement condom use, including pre-exposure prophylaxis in oral or topical microbicide form combined with enhanced HIV/STI risk communication skills and male involvement in prevention and health promotion efforts (Roberson et al, 2013). …”
Section: Discussionsupporting
confidence: 90%
“…Further research, likely with larger samples, is also needed to explore how participation in couple-based observational studies may reinforce or amplify this pattern of increasing social and emotional intimacy and decreasing condom use. If it is the case that couples become less likely to use condoms as their duration of research participation increases, more studies of the of alternative prevention strategies, such as the microbicide acceptability study conducted by Robertson et al (2013), may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in the same population of FSWs on the US–Mexico border [24] found that 89% of participants were highly interested in vaginal PrEP. Although oral PrEP in women has been shown to decrease risk of HIV acquisition when taken consistently, studies of PrEP in the form of vaginal gels have shown inconsistent efficacy to date [8,25].…”
Section: Discussionmentioning
confidence: 99%
“…As with other HIV risk reduction methods, male partners may oppose PrEP use because they think it suggests infidelity, dishonesty, or a casual attitude toward one's partner, 51,[65][66][67][68] which may exacerbate violence for women in abusive relationships. Jealousy and anxiety about potential infidelity are precursors to IPV and have been associated with IPV-related injuries among women.…”
Section: Partner Resistancementioning
confidence: 99%